2018
DOI: 10.1080/15528014.2018.1547066
|View full text |Cite
|
Sign up to set email alerts
|

Feeding the extended family: gender, generation, and socioeconomic disadvantage in food provision to children

Abstract: This paper examines how US parents and grandparents describe their provision of food to preschool-age children. Drawing on forty-nine interviews with sixteen families, most of which were socioeconomically disadvantaged, it is argued that gender and generation intersect in everyday efforts to care for children's eating. The analysis explores gendered divisions of foodwork, highlights the struggles of single mothers, and examines fathers' redefinitions of the paternal role to include feeding and caring for child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 41 publications
2
41
0
2
Order By: Relevance
“…At baseline, mothers’ LBC questionnaire yielded significantly higher picky eating scores compared to fathers’ questionnaires. Although the paternal role increasingly includes feeding and caring for children [25, 26], fathers are still underrepresented in pediatric obesity research [27]. While the present study contributes a very small piece to this puzzle, to our knowledge, no previous study has compared mothers’ and fathers’ perceptions of children’s picky eating behaviors.…”
Section: Discussionmentioning
confidence: 92%
“…At baseline, mothers’ LBC questionnaire yielded significantly higher picky eating scores compared to fathers’ questionnaires. Although the paternal role increasingly includes feeding and caring for children [25, 26], fathers are still underrepresented in pediatric obesity research [27]. While the present study contributes a very small piece to this puzzle, to our knowledge, no previous study has compared mothers’ and fathers’ perceptions of children’s picky eating behaviors.…”
Section: Discussionmentioning
confidence: 92%
“…A total of 20 studies were included in the review (qualitative n = 13, quantitative n = 7). Of the included 20 articles, three stemmed from a single study 39–41 . Although these three articles used the same participants and methods, the study aims and outcomes were different and therefore are treated as separate studies.…”
Section: Resultsmentioning
confidence: 99%
“…This review includes data from 16,321 subjects reported across 20 studies. Of these, 16,064 were classified as parents with 11 studies reporting whether these were mothers ( n = 1,242) or fathers ( n = 21) 39–43,45–47,49,50 . Mean ages of parents were reported in seven studies and ranged from 30 to 35 39–41,46,47,49,52 .…”
Section: Study Characteristicsmentioning
confidence: 99%
“…This food responsibility for significant others is something perhaps most clearly associated with women and motherhood (Cairns, Johnston 2015, Meah 2014a). However, several recent studies (Meah 2017, Molander 2018, Neuman, Eli, Nowicka 2019, Szabo, Koch 2017, including previous publications from this project (Neuman et al 2017a, b), suggest that the feeding of children is becoming an increasingly relevant part of fathering as well. Molander (2011) has conceptualised mothering as a gendered "meta-practice" that governs the everyday feeding of children among single mothers in Stockholm.…”
Section: Prioritised Healthiness and Normative Orientations Of Fathermentioning
confidence: 79%
“…Moreover, as previously argued based on this sample of men, they saw being both food providers for their children and skilled cooks as important aspects of being fathers, partners and modern men in general (Neuman et al 2017a, b). As such, it seems as if a modern form of fathering and a caring masculinity is connected to responsibilities of "properly" feeding children, something of relevance to continued research into gender and food in everyday life (Meah 2017, Molander 2018, Neuman et al 2019, Szabo and Koch 2017. Gender is relational (Connell 1985(Connell , 2012, socially (re)produced and contested through everyday performances.…”
Section: Prioritised Healthiness and Normative Orientations Of Fathermentioning
confidence: 99%